2004
DOI: 10.1055/s-2004-821309
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Secretion is Stimulated by Ethanol Extract of Anemarrhena asphodeloides in Isolated Islet of Healthy Wistar and Diabetic Goto-Kakizaki Rats

Abstract: Ethanol extract of the roots of Anemarrhena asphodeloides contains a substance, TH2, that stimulates insulin secretion both at 3.3 and 16.7 mM glucose in islets of normal Wistar and diabetic GK rats. The mechanism behind TH2-stimulated insulin secretion involves an effect on the exocytotic machinery of the B-cell, mediated via pertussis toxin-sensitive Gi- (or Ge-) proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…Apparently, active phytochemical ingredients with insulin secretogogue properties seem to be present in alcoholic extracts of OI, suggesting the secretogogues to be polar in nature. The herein inferred importance of polar compounds, extractable in alcoholic solvents, in inducing GSIS finds support in the recent reports of alcoholic extracts of many plants showing potential for glucose stimulated insulin secretion from cell lines [19,20]. Some of the active polar compounds also seem to possess insulinomimetic action as seen by the ability of alcoholic extracts to promote glucose uptake in C2C12 Cells.…”
Section: Discussionsupporting
confidence: 75%
“…Apparently, active phytochemical ingredients with insulin secretogogue properties seem to be present in alcoholic extracts of OI, suggesting the secretogogues to be polar in nature. The herein inferred importance of polar compounds, extractable in alcoholic solvents, in inducing GSIS finds support in the recent reports of alcoholic extracts of many plants showing potential for glucose stimulated insulin secretion from cell lines [19,20]. Some of the active polar compounds also seem to possess insulinomimetic action as seen by the ability of alcoholic extracts to promote glucose uptake in C2C12 Cells.…”
Section: Discussionsupporting
confidence: 75%
“…Several studies have confirmed that crude extracts from these herbs have anti-diabetic effects (Grover et al, 2002;Hoa et al, 2004Hoa et al, , 2009. In vivo studies have demonstrated antidiabetic effects of Nelumbo nucifera (Mani et al, 2010;Mukherjee et al, 1997).…”
Section: Introductionmentioning
confidence: 92%
“…Anemarrhena asphodeloides Bunge (Liliaceae) is a perennial herb and widely grows in most parts of China. The Anemarrhena asphodeloides rhizomes have been demonstrated not only to have anti-diabetic activity, platelet aggregation inhibitory activity, diuretic activity, molluscicidal activity, anti-fungal activity and anti-yeast activity, but also to have inhibiting effects on cyclic AMP phosphodiesterase [7][8][9][10][11] . In traditional Chinese medicine, the Anemarrhena asphodeloides rhizomes are used for the treatment of lung disease, fever, diabetes and constipation [12] .…”
Section: Introductionmentioning
confidence: 99%